Concept Ordnung and German communicative style: Problems of intercultural communication - Olga Dmitrievna Kuzmina, Darya Leonidovna Abuzyarova, Svetlana Salavatovna Takhtarova, (Opción, 2019)
The aim of the article is to define the structure of the concept Ordnung and the main features of the German communicative style determined by this cultural dominance. We also used semantic analysis to define the nuclear and peripheral layer of the concept Ordnung as a method. The study showed that the concept Ordnung in these German-speaking ethnosociums is associated with discipline, law-abidance and cleanliness. In conclusion, the cultural dominant Ordnung plays a significant role for representatives of this ethnosocium, which is confirmed by their love of order and punctuality.